Altered brain activities associated with cue reactivity during forced break in subjects with Internet gaming disorder. (March 2020) - Zhang, Jialin; Hu, Yan; Li, Hui; Zheng, Hui; Xiang, Ming; Wang, Ziliang; Dong, Guangheng
Highlights: The recreational Internet game users were included as control group in current study. Create a forced break situation for IGD to explore the neural underpinnings of them. IGD failed to suppress their game cravings after unexpectedly gaming forced break. Abstract: Background: Studies have proven that forced break can elicit strong psychological cravings for addictive behaviors. This phenomenon could create an excellent situation to study the neural underpinnings of addiction. The current study explores brain features during a cue-reactivity task in Internet gaming disorder (IGD) when participants were forced to stop their gaming behaviors. Methods: Forty-nine IGD subjects and forty-nine matched recreational Internet game users (RGU) were asked to complete a cue-reactivity task when their ongoing gaming behaviors were forced to break. We compared their brain responses to gaming cues and tried to find specific features associated with IGD. Results: Compared with RGU, the IGD subjects showed decreased activation in the anterior cingulate cortex (ACC), parahippocampal gyrus, and dorsolateral prefrontal cortex (DLPFC). Significant negative correlations were observed between self-reported gaming cravings and the baseline activation level (bate value) of the ACC, DLPFC, and parahippocampal gyrus. Conclusions: IGD subjects were unable to suppress their gaming cravings after unexpectedly forced break. This result could also explain why RGU subjects are able to play online games without developing dependence.